Systematic review of literature on Group Cognitive Behavior Therapy for Women Victims of Intimate Partner Violence: structure, strategies and therapeutic techniques. (Brazilian Journal of Behavioral and Cognitive Therapy, 2026)
The article presents a systematic review of group interventions based on Cognitive-Behavioral Therapy (CBT) for women victims of intimate partner violence, with the aim of examining the structure of the interventions, as well as the therapeutic strategies and techniques employed. The research, carried out on the Web of Science and VHL databases, utilized the combination of the keywords “Group Therapy” AND “Intimate partner violence”, “Cognitive-behavioral group therapy” AND “Intimate partner violence”, and “Group Psychotherapy” AND “Intimate partner violence”, analyzing thirteen studies published in the last ten years. There was consistent use of strategies such as psychoeducation of emotions, techniques focused on improving self-esteem, social skills, mindfulness and treatment of recurrent psychological disorders in this group, especially Post-Traumatic Stress Disorder. The analysis reinforces the role of group interventions in contexts with a high prevalence of violence against women as essential tools in public health policies.
Keywords: Cognitive Behavioral Therapy; Intimate Partner Violence; Group Psychotherapy